2011
DOI: 10.1093/icesjms/fsr100
|View full text |Cite
|
Sign up to set email alerts
|

The Irish Sea data-enhancement project: comparison of self-sampling and national data-collection programmes—results and experiences

Abstract: Hoare, D., Graham, N., and Schön, P-J. 2011. The Irish Sea data-enhancement project: comparison of self-sampling and national data-collection programmes—results and experiences. – ICES Journal of Marine Science, 68: 1778–1784. The Irish Sea Data Enhancement Pilot (ISDEP) was initiated by the UK and Irish fishing sectors, with the objective of improving the precision of commercial catch data (landings and discards) from vessels engaged in demersal trawling in the Irish Sea (ICES Division VIIa). The programme wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 2 publications
1
21
0
Order By: Relevance
“…At the same time, it would be possible to increase the range of variables to be collected. Indeed, other experiences in participatory sampling showed that fishers can efficiently self-sample length frequency distributions of the catches as well as assess discards (Hoare et al, 2011;Roman et al, 2011;Kraan et al, 2013).…”
Section: Application Of Self-sampling In Fisheries Science and Managementioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, it would be possible to increase the range of variables to be collected. Indeed, other experiences in participatory sampling showed that fishers can efficiently self-sample length frequency distributions of the catches as well as assess discards (Hoare et al, 2011;Roman et al, 2011;Kraan et al, 2013).…”
Section: Application Of Self-sampling In Fisheries Science and Managementioning
confidence: 99%
“…A major problem in the use of self-sampled data for management purposes is related to the fact that fishermen self-sampling remains to be considered by some scientists and managers as lacking rigor, and potentially biased by misreporting (Hoare et al, 2011;Kraan et al, 2013). Fishermen are usually not keen on sharing their own data, because they fear it could be used as evidence for enforcing restrictions in their activities (Kraan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Alterative monitoring and enforcement tools might include self‐sub sampling (Hoare et al . ) and remote electronic monitoring (McElderry ; Kindt‐Larsen et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The physical presence of observers may not always be a necessary condition, given the expense and (occasional) reliability issues of at-sea observers. Alterative monitoring and enforcement tools might include self-sub sampling (Hoare et al 2011) and remote electronic monitoring (McElderry 2008;Kindt-Larsen et al 2011).…”
Section: Challengesmentioning
confidence: 99%
“…The fishing industry, however, offers a unique opportunity to help fisheries and marine environment monitoring requirements. Case studies on fisheries-dependent data (Hoare, Graham, & Schon, 2011;Lordan, Cuaig, Graham, & Rihan, 2011;Pennington & Helle, 2011;Roman, Jacobson, & Cadrin, 2011;Sampson, 2011;Uhmann, Bierman, & van Helmond, 2011) show that the fishing industry can play a central role in addressing data gaps across many fisheries. Experiences from the UK involving the fishing industry in the commissioning and implementation of fishery science projects indicate that fishers have a keen interest in helping provide data that may avert unnecessary precautionary measures being implemented (Armstrong, Payne, Deas, & Catchpole, 2013).…”
Section: Introductionmentioning
confidence: 99%